Gamification of Virtual Learning Environments: A Narrative and User Experience Approach - Palomino, Paula Toledo (2022)
Several educational gamification studies investigate how to encourage students to do specific tasks or progress in learning content. However, many studies are inconclusive about how much gamifying an environment helps or hinders these processes. According to the literature, most existing gamification frameworks are structural (i.e., points, badges, and leaderboards), with few content frameworks (to guide where teachers should use game elements and concepts within the learning content). Furthermore, based on recent systematic literature reviews, no narrative framework exists (i.e., concerned with the students learning path and experience), partly because it is difficult to embed a narrative into a platform other than a game. Based on this premise, the objective of this research was to develop, test, and validate a content gamification framework based on the narrative that the students will experience as they progress in their studies. Our primary target users are teachers, instructional designers or developers who can use the framework to gamify classes or educational systems and, secondly, the students who will undergo the gamified experience. Therefore, we developed four artifacts using user experience (UX) concepts and techniques; all focused on education: (1) a specific narrative definition for gamification, (2) a gamification framework based on narrative and storytelling, (3) a new approachthe Gamification Journeyto personalize gamification strategies, and (4) finally, an application ontology in OWL that connects all concepts. To assess the effectiveness of each artifact, we conducted empirical studies, user tests and interviews with experts. The results demonstrate that it is possible to systematize the use of subjective game elements. These approaches have great potential in the educational field, regarding gamification not as a tool but as an experience, opening a new path for future research.